AN UNUSUAL CASE OF INVASIVE TSHSECRETING PITUITARY MACROADENOMA IN REMISSION AFTER SURGERY - Soh, Shui Boon (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE TSHomas are often large and invasive. Adjunctive therapy is usually required post-surgery. A 36-year-old Chinese Singaporean male presented with thyrotoxic symptoms. He had elevated FT4 of 36.24 pmol/L (10-20), and normal TSH of 1.70 mIU/L (0.4-4.0), consistent in different laboratories. SHBG was elevated at 81.7 nmol/L (15-50). Alpha-subunit was elevated at 3.9 ng/ml ((<0.5); molar ratio to TSH was 15.5. MRI showed a 2.3 x 1.7 x 1.9 cm pituitary mass with suprasellar extension, bowing of optic chiasm, and abutting of bilateral carotid arteries. Other pituitary hormones and visual fields were normal. He underwent trans-sphenoidal surgery. Histology confirmed thyrotroph adenoma. The symptoms resolved promptly. FT4 normalised within 1 week. Initially suppressed TSH normalised 1.5 years postsurgery. MRI 1 year later showed 0.3x0.9x0.7cm pituitary mass. He is now in remission 13 years post-surgery without adjunctive therapy. Though uncommon, invasive macroTSHomas may be cured with surgery. Patients should be counseled appropriately